Methodology for the Evaluation of Magneto-Inertial Orientation Filters in SO(3) - Tosi, Jacopo; Taffoni, Fabrizio; Hussain, Asif; Campolo, Domenico; Formica, Domenico (2019 II Workshop on Metrology for Industry 4.0 and IoT (MetroInd4.0&IoT), 2019)
In the last years, inertial measurement units are playing a primary role in bioengineering for motion tracking research. These devices are cost-effective and can be successfully used for accurate, non-invasive and portable motion tracking.In the literature there is a lack of rigorously assessment in the accuracy estimation of the orientation. Technical specification of commercial systems reported by vendors are presented with caveats and are poorly documented.The objective of this work is to find a standard and reliable methodology, defined in SO(3) orthogonal group, to tune and compare sensor fusion filters used to get orientation from M-IMU sensors. As a matter of fact, each filter exploits some gain parameters to tune the output of the filter. Knowing that, it is important to understand how to tune these parameters, but also find a way to compare all the filters, in order to understand which of them is the best solution to apply.To evaluate this method we have chosen a set of filter already present in the state of the art and we generated, starting from a known trajectory, synthetic M-IMU data to be used as ground truth, in order to compare the orientation angle defined by this trajectory with output of the sensor fusion algorithms.The output error is very low, around 0.005 rad by mean. This results evidences the reliability and efficacy of our method and confirms how the tuning of gain parameters can drive through better performance.